Safflower heterosis for yield and its contributed characters: Safflower heterosis for yield and its contributed characters - SANGITA U FATAK; S J GAHUKAR; R D RATNAPARKHI (Journal of Oilseeds Research, 2023)
Twenty two hybrids were tested using line x tester design involving two cytoplasmic male sterile lines during rabi 2018, using Randomized block design with three replications. Twenty two along with three checks 'A-1, PBNS-12, PKV Pink' were evaluated at the field of Oilseeds Research Unit, Dr. PDKV, Akola during rabi 2019- 2020 to estimate extent of heterosis in safflower genotypes.Among all the crosses, AKS CMS 2A x GMU 1183 (46.15 % and 44.30%) exhibited highly significant and positive average heterosis for number of seeds/plant over mid and better parent. crosses, AKS CMS 2A x GMU 184 (49.26% and 34.44%) exhibited highly significant and positive average heterosis for 100 seed weight, whereas, cross AKS CMS 2A x GMU 5149 (15.28% and 9.32%) exhibited highly significant and positive average heterosis for volume weight. The highest heterosis and heterobeltiosis in desirable direction were recorded for seed yield/plant in AKS CMS 2A x GMU 1654 (246.96%) and the cross AKS CMS 3A x GMU 1183 (206.75%) showed highest and significantly positive standard heterosis over the checks i.e. PKV PINK, AKS 207 and PBNS-12.